Pengembangan Computer Assisted Instructional Integrated Science Materi “Hujan” di Sekolah Dasar - Setria Utama Rizal; Din Azwar Uswatun; Astri Sutisnawati; Rifki Aditia (Al-Mudarris, 2020)
The lack of learning media is one indicator of science learning less favored by elementary school students. The use of instructional media can overcome students' difficulties in understanding contextually material. The purpose of this research is to produce integrated learning media Computer Assisted Instructional learning material "rain" material in improving critical thinking skills of third grade elementary school students. This research method uses research & development with the Borg & Gall development model and field trials using one-group pretest-posttest design at SDIT Al-Khoiriyah Al-Husna Sukabumi. Data collection techniques using interviews, observation, questionnaires, and tests. Data collection instruments included interview guidelines, observation sheets, questionnaire sheets, and test questions. The results of this study are in the form of learning products for Computer Assisted Instructional integrated science elementary school with "rain" material. The results of the product validation show that the integrated Computer Assisted Instructional learning media is appropriate for use in elementary science learning with an average rating from the "Very Good" category validator. Field trial results show that the integrated Computer Assisted Instructional elementary school learning media with "rain" material is effectively used in the elementary science learning process to improve students' critical thinking skills with a gain of 0.81. So that the results of this study can be used in the learning process of science in students of SDIT Al-Khoiriyah Al-Husna Sukabumi and developed in other SD / MI.